Liquid conditioning composition comprising chitosan
By adding chitosan and alkyl quaternary ammonium salts to the liquid conditioning composition and using a fragrance delivery system, the contradiction between high viscosity and good odor in the liquid conditioning composition is solved, and the fragrance release performance and product performance are improved.
Patent Information
- Application Number
- CN202410729853.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-06-06
- Publication Date
- 2024-12-31
AI Technical Summary
When existing liquid conditioning compositions pursue good pure product odor (NPO) and high viscosity, higher viscosity will have a negative impact on the release of free fragrances, resulting in a degradation of product performance and it is difficult to meet both requirements at the same time.
Add appropriate amount of chitosan to the liquid conditioning composition, combining alkyl ester quaternary ammonium salts and free fragrances, optimize the viscosity and fragrance release properties of the composition, improve the performance of the composition by treating chitosan by acid and using a fragrance delivery system .
It effectively improves the release performance of spices, improves the pure product odor (NPO) and viscosity of the product, extends the duration of spices, and meets the needs of high viscosity and good odor.
Smart Images

Figure CN119221284A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to liquid conditioning compositions comprising chitosan. The present disclosure also relates to methods and uses of liquid conditioning compositions comprising chitosan. Background Art
[0002] Liquid conditioning compositions are desired by both manufacturers and consumers to have a desirable pure product odor (NPO). When shopping, consumers often open bottles on supermarket shelves, smell the products, and choose what they want to buy based on the smell of the products. Consumers also desire products to have a thick consistency, as high viscosity conveys a luxurious use experience and better performance.
[0003] Unfortunately, these characteristics of a desirable liquid conditioning composition (i.e., good NPO and high viscosity) are not mutually exclusive, as higher viscosity in the finished product can negatively impact the release of free fragrance, thereby reducing the NPO of the product. Thus, there is a continuing interest in discovering new and useful liquid conditioning products having desirable NPO and body. Summary of the invention
[0004] The present disclosure relates to liquid conditioning compositions, such as liquid fabric enhancers, comprising an amount of chitosan.
[0005] As a non-limiting example, the present disclosure is directed to a liquid conditioning composition comprising from about 2% to about 8%, by weight of the composition, of an alkyl esterquat ("esterquat") softening active; from 0.0001% to about 0.025%, by weight of the composition, of chitosan; and from 0.01% to about 5%, by weight of the composition, of free fragrance oil; wherein the composition has a viscosity of from about 80 cPs to about 300 cPs.
[0006] The present disclosure also relates to a method of treating a surface, wherein the method comprises the step of contacting a surface, preferably a fabric, more preferably a fabric comprising cotton fibers, with a liquid conditioning composition according to the present disclosure, optionally in the presence of water.
[0007] The present disclosure also relates to concentrated softening active compositions that can be used to prepare the liquid conditioning compositions of the present disclosure, wherein the concentrated softening active composition comprises from about 0.0001% to about 0.025% chitosan, as described herein, by weight of the composition; and a liquid carrier selected from the group consisting of water, a surfactant or an organic solvent.
[0008] The present disclosure also relates to the use of chitosan, preferably as part of a liquid conditioning composition, to provide pure product smell (NPO) benefits, wherein the chitosan has a weight average molecular weight (Mw) of about 70 kDa to about 600 kDa. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 is a photograph of an exemplary liquid fabric conditioner sample showing a Failure Level 1 evaluation score using the method for evaluating phase stability of LFE products as detailed herein;
[0010] Figure 2 is a photograph of an exemplary liquid fabric conditioner sample showing a Failure Level 2 evaluation score using the method for evaluating phase stability of LFE products as detailed herein;
[0011] Figure 3 is a photograph of an exemplary liquid fabric conditioner sample showing a Failure Level 3 evaluation score using the method for evaluating phase stability of LFE products as detailed herein;
[0012] Figure 4 is a photograph of an exemplary liquid fabric conditioner sample showing a Failure Level 4 evaluation score using the method for evaluating phase stability of LFE products as detailed herein;
[0013] Figure 5 is a photograph of an exemplary liquid fabric conditioner sample showing a Failure Level 5 evaluation score using the method for evaluating phase stability of LFE products as detailed herein;
[0014] Figure 6 a graph detailing the neat product odor headspace values of the liquid fabric conditioner samples; and
[0015] Figure 7 A photograph of an aged commercially available liquid fabric enhancer product with added chitosan. DETAILED DESCRIPTION
[0016] The present disclosure relates to liquid conditioning compositions, such as liquid fabric enhancers, which contain a certain amount of chitosan. It has been surprisingly found that adding chitosan to liquid conditioning compositions can improve the release of fragrances and thus increase NPO. The materials, compositions, methods and uses of such liquid conditioning compositions are described in more detail below.
[0017] As used herein, the articles "a" and "an" when used in a claim are understood to refer to one or more of the things protected or described by the claim. As used herein, the terms "comprising," "including," and "containing" are intended to be non-limiting. The compositions of the present disclosure may comprise, consist essentially of, or consist of the components of the present disclosure.
[0018] The term "substantially free" may be used herein. This means that the referenced material is very small, not intentionally added to the composition to form part of the composition, or preferably the referenced material is not present at analytically detectable levels. This refers to compositions in which the referenced material is present only as an impurity in one of the other materials that are intentionally added. If present, the referenced material may be present at a level of less than 1%, or less than 0.1%, or less than 0.01%, or even 0% by weight of the composition.
[0019] As used herein, the phrase "fabric care composition" includes compositions and formulations designed for treating fabrics. Such compositions include, but are not limited to, laundry cleaning compositions and detergents, fabric softening compositions, fabric enhancing compositions, fabric refreshing compositions, laundry pre-washes, laundry pre-treaters, laundry additives, spray-on products, dry cleaning agents or compositions, laundry rinse additives, washing additives, post-rinse fabric treatment agents, ironing aids, unit dose formulations, delayed delivery formulations, detergents on or included in porous substrates or nonwoven sheets, and other suitable forms that are apparent to those skilled in the art according to the teachings herein. Such compositions can be used as laundry pre-treaters, laundry post-treaters, or can be added during the rinse cycle or wash cycle of a laundry operation.
[0020] Unless otherwise indicated, all component or composition levels are in terms of the active portion of that component or composition and are exclusive of impurities, for example, residual solvents or by-products, which may be present in commercially available sources of such component or composition.
[0021] Unless otherwise indicated, all temperatures herein are in degrees Celsius (° C.) Unless otherwise indicated, all measurements herein are made at 20° C. and atmospheric pressure.
[0022] In all embodiments of the present disclosure, unless otherwise specifically stated, all percentages are by weight of the total composition. Unless otherwise specifically stated, all ratios are by weight.
[0023] It should be understood that each maximum numerical limitation given throughout this specification includes each lower numerical limitation, as if such lower numerical limitations were expressly written herein. Each minimum numerical limitation given throughout this specification will include each higher numerical limitation, as if such higher numerical limitations were expressly written herein. Each numerical range given throughout this specification will include each narrower numerical range falling within such wider numerical range, as if such narrower numerical ranges were all expressly written herein.
[0024] Liquid conditioning compositions
[0025] The present disclosure relates to liquid conditioning compositions.The liquid conditioning composition may be a fabric care composition or a hair care composition, preferably a liquid fabric enhancer or a hair conditioner, more preferably a liquid fabric enhancer.
[0026] The liquid conditioning composition may have a viscosity of about 50 cPs to about 300 cPs (about 50 mPa·s to about 300 mPa·s), or about 80 cPs to about 300 cPs, or about 90 cPs to about 250 cPs, or preferably about 150 cPs to about 250 cPs. The viscosity is measured using a Brookfield viscometer, spindle No. 2, at a speed of 60 RPM / s at about 22° C. Compositions having viscosities lower than those provided herein may be considered too thin and considered "cheap"; compositions having relatively high viscosities may present challenges to processing or distribution.
[0027] Liquid conditioning compositions may be characterized by a dynamic yield stress. For example, a fabric softener composition may have a dynamic yield stress at 20°C of 0.001 Pa to 1.0 Pa, preferably 0.005 Pa to 0.8 Pa, more preferably 0.01 Pa to 0.5 Pa. In the case of liquid compositions comprising suspended particles or encapsulated benefit agents, the absence of a dynamic yield stress may result in phase instabilities, such as particle demixing or settling. Very high dynamic yield stress may result in undesirable air entrapment during filling of bottles with fabric softener compositions. The dynamic yield stress is determined according to the method provided in the Test Methods section below.
[0028] The liquid conditioning compositions of the present disclosure may be characterized by a pH of from about 2 to about 12, or from about 2 to about 8.5, or from about 2 to about 7, or from about 2 to about 5. The compositions of the present disclosure may have a pH of from about 2 to about 4, preferably from about 2 to about 3.7, more preferably from about 2 to about 3.5, preferably in the form of an aqueous liquid. It is believed that an acidic pH level is favorable for the stability of the esterquat. The pH of the composition is determined by dissolving / dispersing the composition in deionized water at about 20°C to form a 10% concentration solution.
[0029] The liquid conditioning composition of the present disclosure may contain water. The liquid conditioning composition may contain from about 40% to about 98%, or from about 50% to about 96%, or from about 75% to about 95%, or from about 80% to about 94% water by weight of the composition. The water content may be selected so that the amount of softening active is balanced to the desired level. The selection of esterquats described herein is believed to be particularly useful in compositions having relatively high water contents, as such ingredients can provide both performance and viscosity-increasing benefits.
[0030] The liquid conditioning composition may be packaged in a pour bottle. The liquid conditioning composition may be packaged in an aerosol can or other spray bottle. The packaging may be translucent or transparent.
[0031] The liquid conditioning compositions of the present disclosure may also include one or more of the ingredients listed below.
[0032] Chitosan
[0033] The liquid conditioning compositions of the present disclosure include a certain level of chitosan. The liquid conditioning compositions of the present disclosure may include from about 0.0001% to about 0.025%, or from about 0.001% to about 0.025%, or from about 0.001% to about 0.02%, or from about 0.0015% to about 0.015%, or from about 0.002% to about 0.01% chitosan by weight of the composition.
[0034] Chitosan may be treated partially or completely with a redox initiator. The redox initiator may be selected from the group consisting of persulfates, peroxides and combinations thereof. Suitable redox initiators may include ammonium persulfate, sodium persulfate, potassium persulfate, cesium persulfate, benzoyl peroxide, hydrogen peroxide and mixtures thereof. The redox initiator may preferably be selected from sodium persulfate, hydrogen peroxide or mixtures thereof. The redox initiator may preferably be a persulfate. The redox initiator may preferably be a peroxide. The redox initiator may preferably be sodium persulfate. The treatment of chitosan with a redox initiator is typically carried out in an aqueous phase, preferably an acidic aqueous phase, and then an emulsion is formed that results in the formation of delivery particles. In the reaction to form the modified chitosan, the redox initiator and chitosan may be present in a weight ratio of about 90:10 to about 0.01:99.99, preferably about 50:50 to about 1:99, more preferably about 30:70 to about 3:97.
[0035] Chitosan can be partially or completely acid-treated chitosan. For example, chitosan (which can be referred to as raw chitosan or parent chitosan before acid treatment) can be treated with acid at a temperature of about 25°C to about 99°C, preferably about 75°C to about 95°C, at a pH of 6.5 or less for at least one hour, preferably about one hour to about three hours, or the time period required to obtain a chitosan solution viscosity of no more than about 1500cps, or even no more than 500cps. The acid can be selected from a strong acid (such as hydrochloric acid), an organic acid (such as formic acid or acetic acid) or a mixture thereof. Chitosan can preferably be acid-treated at a pH of 2 to 6.5, preferably a pH of about 3 to about 6, or even a pH of 4 to 6.
[0036] Chitosan, more preferably acid-treated chitosan, may be characterized by a molecular weight of about 70 kDa to about 600 kDa, preferably about 90 kDa to about 400 kDa, even more preferably about 100 kDa to about 300 kDa, even more preferably about 100 kDa to about 250 kDa. Without wishing to be bound by theory, it is believed that biopolymers characterized by relatively low molecular weight are less effective in forming suitable delivery particles, while those with relatively high molecular weights are often difficult to process. Methods for determining chitosan molecular weight and related parameters are provided in the test methods section below, and use gel permeation chromatography with multi-angle light scattering and refractive index detection (GPC-MALS / RI) technology.
[0037] Chitosan can be characterized by a degree of deacetylation of at least 50%, preferably from about 50% to about 99%, more preferably from about 75% to about 90%, and even more preferably from about 80% to about 85%. The degree of deacetylation can affect the solubility of chitosan, which in turn can affect its reactivity or behavior in the process of forming a particle shell. For example, too low a degree of deacetylation (e.g., less than 50%) can cause the chitosan to be relatively insoluble and relatively unreactive. A relatively high degree of deacetylation can cause the chitosan to be very soluble, thereby causing relatively little chitosan to travel to the oil / water interface during shell formation.
[0038] When chitosan is present, it may include anionically modified chitosan, cationically modified chitosan, or a combination thereof. Modification of chitosan in an anionic and / or cationic manner may alter the characteristics of the shell of the delivery particle, for example by changing the surface charge and / or zeta potential, which may affect the deposition efficiency and / or formulation compatibility of the particle.
[0039] Esterquat
[0040] The liquid conditioning compositions of the present disclosure contain certain alkyl quaternary ammonium ester materials, also referred to herein as "esterquats". Such esterquats can be used to provide conditioning benefits to target fabrics, such as softness, anti-wrinkle, anti-static, conditioning, anti-stretch, color and / or appearance benefits. In addition, the esterquats of the present disclosure can be used to increase viscosity at relatively low active levels.
[0041] The liquid conditioning composition may comprise from about 2% to 20%, or from about 2% to about 15%, or from about 2% to about 12%, by weight of the composition of an esterquat softening active, as described in more detail below. The composition may comprise from about 2% to about 10%, preferably from about 2% to about 8%, more preferably from about 3% to about 7%, even more preferably from about 3% to about 6%, by weight of the composition of an esterquat softening active. The composition may comprise from about 2% to about 8%, by weight of the composition of an esterquat softening active.
[0042] Suitable quaternary ammonium ester softening actives include, but are not limited to, materials selected from the group consisting of monoester quaternary ammonium salts, diester quaternary ammonium salts, triester quaternary ammonium salts, and mixtures thereof. Preferably, based on the total weight of the quaternary ammonium ester softening active, the level of monoester quaternary ammonium salts is from 2.0% to 40.0%, the level of diester quaternary ammonium salts is from 40.0% to 98.0%, and the level of triester quaternary ammonium salts is from 0.0% to 25.0%.
[0043] The quaternary ammonium ester softening active may comprise a compound of the formula:
[0044] {R2(4-m)-N+-[XY-R1]m}A-
[0045] in:
[0046] m is 1, 2, or 3, provided that the value of each m is the same;
[0047] Each R1 is independently a hydrocarbon group, or a branched hydrocarbon group, preferably R1 is a linear chain, more preferably R1 is a partially unsaturated linear alkyl chain;
[0048] Each R2 is independently a C1-C3 alkyl or hydroxyalkyl group, preferably R2 is selected from methyl, ethyl, propyl, hydroxyethyl, 2-hydroxypropyl, 1-methyl-2-hydroxyethyl, poly (C2-C3 alkoxy), polyethoxy, benzyl;
[0049] Each X is independently -(CH2)n-, -CH2-CH(CH3)-, or -CH-(CH3)-CH2-; and
[0050] Each n is independently 1, 2, 3 or 4, preferably each n is 2;
[0051] Each Y is independently -O-(O)C- or -C(O)-O-;
[0052] A- is independently selected from the group consisting of chloride, methyl sulfate and ethyl sulfate, preferably A- is selected from the group consisting of chloride and methyl sulfate;
[0053] Provided that when Y is -O-(O)C-, the sum of the carbons in each R1 is from 13 to 21, preferably from 13 to 19. Preferably, X is -CH2-CH(CH3)- or -CH(CH3)-CH2- to improve the hydrolytic stability of the quaternary ammonium ester softening active, thereby further improving the stability of the liquid fabric softener composition.
[0054] Due to the balance between processing properties and odor of the quaternary ammonium ester softening actives, in preferred liquid fabric softener compositions the parent fatty acid from which the quaternary ammonium fabric softening active is formed has an iodine value of from 0 to 100, more preferably from 10 to 60, even more preferably from 15 to 45.
[0055] Esterquat softening actives are derived from fatty acid feedstocks. The fatty acid feedstocks include fatty acids. The fatty acid feedstocks may be partially hydrogenated, as such processes may provide the desired amount of trans fatty acids. As used herein, "partially hydrogenated" means that the fatty acids themselves undergo a partial hydrogenation process, or the oil from which the fatty acids are derived undergoes a hydrogenation process, or both. Additionally, the partial hydrogenation process may reduce the amount of diunsaturated fatty acids, the presence of which may result in color and / or odor instability in the final product.
[0056] Lipid acid can be derived from plants. Suitable sources of plant-derived lipid acid can include vegetable oils, such as canola oil, safflower oil, peanut oil, sunflower oil, sesame oil, rapeseed oil, cottonseed oil, corn oil, soybean oil, tall oil, rice bran oil, palm oil, palm kernel oil, coconut oil, other tropical palm oils, linseed oil, tung oil, etc. Preferably, the fatty acid raw material comprises the lipid acid derived from cottonseed, rapeseed, sunflower seed or soybean, preferably the lipid acid derived from cottonseed. These materials are particularly preferred because they tend to produce lipid acids with required trans unsaturated content when partially hydrogenated. Therefore, the fatty acid raw material can comprise partially hydrogenated fatty acids, which are derived from plants, preferably derived from vegetable oils, more preferably derived from canola oil, safflower oil, peanut oil, sunflower oil, sesame oil, rapeseed oil, cottonseed oil, corn oil, soybean oil, tall oil, rice bran oil, palm oil, palm kernel oil, coconut oil, other tropical palm oils, linseed oil, tung oil or their mixtures, more preferably derived from cottonseed, rapeseed, sunflower seeds, soybean or their mixtures. Fatty acids can at least partially comprise partially hydrogenated fatty acids derived from cottonseed oil, because such materials are considered to have a favorable distribution of fatty acid types and trans-unsaturated bonds.
[0057] Fatty acid can include an alkyl moiety containing an average weight of about 13 to about 22 carbon atoms, or about 14 to about 20 carbon atoms, preferably about 16 to about 18 carbon atoms, wherein the carbon count includes the carbon of the carboxyl group. The fatty acid population can exist with a distribution of alkyl chain sizes. The feature of a particular fatty acid can be the carbon number in its alkyl moiety. For example, a fatty acid with 16 carbons in the alkyl moiety can be referred to as a "C16 fatty acid." Similarly, a fatty acid with 18 carbons in the alkyl moiety can be referred to as a "C18 fatty acid."
[0058] The fatty acid feedstock may contain less than 25% C16 fatty acids by weight of the fatty acid feedstock. The fatty acid feedstock may contain from about 5% to about 25%, preferably from about 10% to about 25%, more preferably from about 15% to about 25%, even more preferably from about 20% to about 25% C16 fatty acids by weight of the fatty acid feedstock. It may be desirable to limit the relative amount of C16 fatty acids in the fatty acid feedstock. Without wishing to be bound by theory, it is believed that a relatively high proportion of C16 fatty acids (especially relative to C18 fatty acids) can result in a relatively low viscosity in the final product.
[0059] Additionally, or alternatively, it may be desirable to have at least a certain minimum amount of C16 fatty acids in the fatty acid feedstock (e.g., at least 10%, preferably at least 15%, even more preferably at least 20% by weight based on the weight of the fatty acid feedstock). Such materials can help improve processability because esterquats based on materials including C16 fatty acids tend to have lower melting points and can be relatively easier to disperse than esterquats produced primarily from more crystalline C18 (and / or C18-trans) fatty acids having low / zero levels of C16.
[0060] The alkyl quaternary ammonium ester softening actives may comprise compounds formed from unsaturated fatty acids, meaning that the fatty acids contain at least one double bond in the alkyl portion. The fatty acids may be monounsaturated (one double bond), or they may be diunsaturated (or diunsaturated; two double bonds). Preferably, the majority of the unsaturated fatty acids in the fatty acid feedstock are monounsaturated.
[0061] The fatty acid may comprise an unsaturated C18 chain, which may comprise a single double bond ("C18: 1") or may be di-unsaturated ("C18: 2"). (For reference, fatty acids having a saturated C18 chain may be referred to as "C18: 0"). The fatty acid feedstock may comprise from about 50% to about 85%, preferably from about 60% to about 80%, more preferably from about 70% to about 80%, of C18 fatty acids, whether saturated or unsaturated, by weight of the fatty acid feedstock. The fatty acid feedstock may comprise from about 20% to about 60%, preferably from about 40% to about 60%, more preferably from about 45% to about 55%, of C18: 0 fatty acids, by weight of the composition. The fatty acid feedstock may comprise from about 15% to about 50%, preferably from about 15% to about 30%, more preferably from about 18% to about 25%, of C18: 1 fatty acids, by weight of the composition. The fatty acid feedstock may comprise from 0% (e.g., none) to about 20%, or from about 0% to about 15%, or from about 0% to about 10%, or from about 0% to about 5% C18:2 fatty acids by weight of the fatty acid feedstock. The fatty acid feedstock may comprise from about 1% to about 15%, preferably from about 5% to about 10% C18:2 fatty acids by weight of the fatty acid feedstock.
[0062] Esterquat materials can be prepared using a two-step synthetic process. First, the esteramine can be produced by an esterification reaction using a fatty acid and an alkanolamine. In the second step, the product can be quaternized using an alkylating agent.
[0063] In addition to the above-mentioned esterquats, the liquid conditioning compositions of the present disclosure may also contain other conditioning agents. The other conditioning agents may be selected from the group consisting of quaternary ammonium ester compounds other than those described above, silicones, non-ester quaternary ammonium compounds, amines, fatty esters, sucrose esters, silicones, dispersible polyolefins, polysaccharides, fatty acids, softening or conditioning oils, polymer latexes, glyceride copolymers, or combinations thereof.
[0064] Examples of suitable quaternary ammonium ester softening actives are available from KAO Chemicals under the trade name AT-1 and AT-7590, from Evonik under the trade name WE16DPG, WE18, WE20, WE28 and 38DPG, from Stepan under the trade name GA90, VR90, VK90, VA90, DC90 and VL90A was purchased commercially.
[0065] These types of reagents and general methods for preparing them are disclosed in USPN 4,137,180.
[0066] Fragrances and Fragrance Delivery Systems
[0067] The liquid conditioning composition may comprise a perfume, a perfume delivery system, or a combination thereof. Such a system may improve the freshness performance of the compositions described herein. Specifically, the perfume delivery system may promote improved freshness performance by increasing deposition efficiency, promoting perfume release at different contact points, and / or extending perfume performance duration.
[0068] Pure spices
[0069] Perfume may be present as a pure oil, sometimes referred to as, for example, "free" perfume, unencapsulated perfume, or free perfume oil. The liquid conditioning composition may contain from about 0.01% to about 5%, or from about 0.05% to about 4%, or from about 0.1% to about 3%, or from about 0.5% to about 2%, by weight of the composition, of free perfume oil.
[0070] The absolute oil may contain perfume raw materials such as 3-(4-tert-butylphenyl)-2-methylpropanal, 3-(4-tert-butylphenyl)-propanal, 3-(4-isopropylphenyl)-2-methylpropanal, 3-(3,4-methylenedioxyphenyl)-2-methylpropanal and 2,6-dimethyl-5-heptanal, α-damascone, β-damascone, γ-damascone, β-damascone, 6,7-dihydro-1,1,2,3,3-pentamethyl-4(5H)-indanone, methyl-7,3-dihydro-2H-1,5-benzodioxin-3-one, 2-[2-( 4-methyl-3-cyclohexenyl-1-yl)propyl]cyclopentan-2-one, 2-sec-butylcyclohexanone, and β-dihydroionone, linalool, ethyl linalool, tetrahydrolinalool and dihydromyrcenol; silicone oil, wax, such as polyethylene wax; essential oil, such as fish oil, jasmine, camphor, lavender; skin cooling agent, such as menthol, methyl lactate; vitamin, such as vitamin A and vitamin E; sunscreen; glycerol; catalyst, such as manganese catalyst or bleaching catalyst; bleaching agent particles, such as perborate; silica particles; antiperspirant active substance; cationic polymer and mixtures thereof. Suitable benefit agents can be purchased from Givaudan Corp. (Mount Olive, New Jersey, USA), International Flavors & Fragrances Corp. (South Brunswick, New Jersey, USA), Firmenich Company (Geneva, Switzerland), or Encapsys Company (Appleton, Wisconsin, USA). As used herein, "fragrance raw materials" means one or more of the following ingredients: fragrance essential oils; fragrance compounds; pro-fragrances; materials provided with fragrance essential oils, fragrance compounds and / or pro-fragrances, including stabilizers, diluents, processing aids and contaminants; and any materials that normally accompany fragrance essential oils, fragrance compounds and / or pro-fragrances.
[0071] Fragrance delivery systems
[0072] The fragrance delivery system may comprise an encapsulate, such as an encapsulate in which a core is surrounded by a wall material (a "core-shell encapsulate"); the core may comprise a fragrance and an optional partition modifier (e.g., isopropyl myristate). The wall material may comprise melamine, polyacrylamide, silicone, silica, polystyrene, polyurea, polyurethane, polyacrylate-based materials, polyacrylate-based materials, gelatin, styrene malic anhydride, polyamide, aromatic alcohols, polyvinyl alcohol, or mixtures thereof. Melamine wall materials may comprise melamine cross-linked with formaldehyde, melamine-dimethoxyethanol cross-linked with formaldehyde, and mixtures thereof; encapsulation with such wall materials may be used in combination with formaldehyde scavengers such as acetoacetamide, urea, or derivatives thereof. Polyacrylate-based wall materials may include polyacrylates formed from methyl methacrylate / dimethylaminomethyl methacrylate, polyacrylates formed from amine acrylate and / or methacrylate and strong acids, polyacrylates formed from carboxylic acid acrylate and / or methacrylate monomers and strong bases, polyacrylates formed from amine acrylate and / or methacrylate monomers and carboxylic acid acrylate and / or carboxylic acid methacrylate monomers, and mixtures thereof.
[0073] Wall materials based on polyacrylic acid esters may include polyacrylic acid esters formed from alkyl and / or glycidyl esters of acrylic acid and / or methacrylic acid, acrylates and / or methacrylates carrying hydroxyl and / or carboxyl groups, and allyl glucamide, and mixtures thereof.
[0074] Wall materials based on aromatic alcohols include aryloxyalkanols, arylalkanols and oligomeric alkanol aryl ethers. They may also contain aromatic compounds with at least one free hydroxyl group, particularly preferably at least two directly aromatically coupled free hydroxyl groups, wherein it is particularly preferred if at least two free hydroxyl groups are directly coupled to an aromatic ring and more particularly preferably positioned in the meta position relative to each other. Preferably, the aromatic alcohol is selected from phenol, cresols (o-cresol, m-cresol and p-cresol), naphthols (α-naphthol and β-naphthol), and thymol, as well as ethylphenol, propylphenol, fluorophenol and methoxyphenol.
[0075] The polyurea-based wall material may comprise a polyisocyanate. The shell of the delivery particle may comprise a polymer material that may be a reaction product of a polyisocyanate and chitosan. The shell may comprise a polyurea resin, wherein the polyurea resin comprises a reaction product of a polyisocyanate and chitosan. The delivery particles of the present disclosure may be considered to be polyurea delivery particles and include a polyurea-chitosan shell. (As used herein, "shell" and "wall" are used interchangeably with respect to delivery particles unless otherwise indicated.) The shell may be derived from isocyanates and chitosan.
[0076] Delivery particles can be prepared according to a method comprising the following steps: forming an aqueous phase comprising chitosan in an aqueous acidic medium; forming an oil phase comprising dissolving at least one beneficial agent and at least one polyisocyanate together; forming an emulsion by mixing the aqueous phase and the oil phase into an excess of the aqueous phase under high shear stirring, thereby forming droplets of the oil phase and the beneficial agent dispersed in the aqueous phase; curing the emulsion by heating for a time sufficient to form a shell at the interface of the droplet and the aqueous phase, the shell comprising the reaction product of the polyisocyanate and chitosan, and the shell surrounding the core of the droplet comprising the oil phase and the beneficial agent. A diluent, such as isopropyl myristate, can be used to adjust the hydrophilicity of the oil phase. The oil phase is then added to the aqueous phase and milled at high speed to obtain the target size. The emulsion is then cured in one or more heating steps.
[0077] The temperature and time are selected to be sufficient to form and solidify the shell at the interface of the droplets of the oil phase and the aqueous continuous phase. For example, the emulsion is heated to 85°C over 60 minutes and then held at 85°C for 360 minutes to solidify the particles. The slurry is then cooled to room temperature.
[0078] The weight percentage of the shell may be chitosan (as defined herein in the chitosan section) from about 21% to about 95% of the shell. The ratio of isocyanate monomer, oligomer or prepolymer to chitosan may be as high as 1:10 by weight.
[0079] The polyisocyanate may be an aliphatic or aromatic monomer, oligomer or prepolymer usefully containing two or more isocyanate functional groups. The polyisocyanate may preferably be selected from the group comprising toluene diisocyanate, trimethylolpropane adducts of toluene diisocyanate and trimethylolpropane adducts of xylylene diisocyanate, methylene diphenyl isocyanate, toluene diisocyanate, tetramethylxylidine diisocyanate, naphthalene-1,5-diisocyanate and phenylene diisocyanate.
[0080] Polyisocyanates can be selected from aromatic toluene diisocyanates and derivatives thereof used in the wall formation of the encapsulate, or aliphatic monomers, oligomers or prepolymers, such as hexamethylene diisocyanate and dimers or trimers thereof, or 3,3,5-trimethyl-5-isocyanatomethyl-1-isocyanatocyclohexane tetramethylene diisocyanate. Polyisocyanates can be selected from 1,3-diisocyanato-2-methylbenzene, hydrogenated MDI, bis(4-isocyanatocyclohexyl)methane, dicyclohexylmethane-4,4'-diisocyanate, and oligomers and prepolymers thereof. This enumeration is exemplary and is not intended to limit the polyisocyanates that can be used in the present disclosure.
[0081] The polyisocyanates useful in the present invention include isocyanate monomers, oligomers or prepolymers having at least two isocyanate groups, or dimers or trimers thereof. Optimal crosslinking can be achieved using polyisocyanates having at least three functional groups.
[0082] For the purposes of this disclosure, polyisocyanates are understood to encompass any polyisocyanate having at least two isocyanate groups and containing an aliphatic or aromatic moiety in a monomer, oligomer or prepolymer. If aromatic, the aromatic moiety may include a phenyl, toluoyl, xylyl, naphthyl or diphenyl moiety, more preferably a toluoyl or xylyl moiety. Aromatic polyisocyanates for the purposes of this document may include diisocyanate derivatives such as biuret and polyisocyanurate. The polyisocyanate, when aromatic, may be, but is not limited to, methylene diphenyl isocyanate, toluene diisocyanate, tetramethylxylidine diisocyanate, polyisocyanurate of toluene diisocyanate (available from Bayer under the trade name RC is commercially available), trimethylolpropane adduct of toluene diisocyanate (available from Bayer under the trade name L75 is commercially available) or a trimethylolpropane adduct of xylylene diisocyanate (available from Mitsui Chemicals under the trade name D-110N is commercially available), naphthalene-1,5-diisocyanate, and phenylene diisocyanate.
[0083] Aromatic polyisocyanates are preferred; however, aliphatic polyisocyanates and blends thereof may be useful. Aliphatic polyisocyanates are understood to be polyisocyanates that do not contain any aromatic moieties. Aliphatic polyisocyanates include trimers of hexamethylene diisocyanate, trimers of isophorone diisocyanate, trimethylolpropane adducts of hexamethylene diisocyanate (available from Mitsui Chemicals), or biuret of hexamethylene diisocyanate (available from Bayer under the trade name N 100 was purchased commercially).
[0084] When tested according to test method OECD 301B, the shell may degrade by at least 50% after 20 days (or less). When tested according to test method OECD 301B, the shell may preferably degrade by at least 60% of its mass after 60 days (or less). The shell may degrade by 30% to 100%, preferably 40% to 100%, 50% to 100%, 60% to 100% or 60% to 95% after 60 days, preferably 50 days, more preferably 40 days, more preferably 28 days, more preferably 14 days.
[0085] The composition may comprise from about 0.05% to about 20%, or from about 0.05% to about 10%, or from about 0.1% to about 5%, or from about 0.2% to about 2% delivery particles by weight of the composition. The composition may comprise a sufficient amount of delivery particles to provide the composition with from about 0.05% to about 10%, or from about 0.1% to about 5%, or from about 0.1% to about 2% of encapsulated benefit agents, which may preferably be fragrance raw materials, by weight of the composition. When the amount or weight percentage of delivery particles is discussed herein, it means the sum of the wall material and the core material.
[0086] Delivery particles according to the present disclosure may be characterized by a volume weighted median particle size of about 1 micron to about 100 microns, preferably about 10 microns to about 100 microns, preferably about 15 microns to about 50 microns, more preferably about 20 microns to about 40 microns, even more preferably about 20 microns to about 30 microns. Different particle sizes can be obtained by controlling the droplet size during the emulsification process.
[0087] The delivery particle may be characterized by a core to shell ratio of up to 85:15, up to 90:10, up to 99:1, or even 99.5:0.5, based on weight.
[0088] The encapsulate may be coated with a deposition aid, a cationic polymer, a nonionic polymer, an anionic polymer or a mixture thereof. Suitable polymers may be selected from the group consisting of polyvinyl formaldehyde, partially hydroxylated polyvinyl formaldehyde, polyvinyl amine, polyethylene imine, ethoxylated polyethylene imine, polyvinyl alcohol, polyacrylate, polysaccharide (e.g. chitosan) and combinations thereof.
[0089] The fragrance delivery system may comprise particles comprising a graft copolymer and a fragrance material, wherein the graft copolymer comprises a polyalkylene glycol (eg polyethylene glycol) as a graft base and one or more side chains comprising vinyl acetate moieties.
[0090] The fragrance delivery system may comprise a pro-fragrance, such as a silicone-based pro-fragrance, wherein the fragrance raw material is associated (eg, via covalent bonding) with a polymer (eg, a silicone polymer) when delivered to a surface and is released upon or after treatment of the surface with the composition.
[0091] The fragrance delivery system may comprise self-assembled particles, which are composed of rosin materials, such as rosin, wood rosin, tall oil rosin or their derivatives, preferably their ester derivatives, and even more preferably their glyceride derivatives. The particles can be obtained by a self-assembly method. The self-assembly method involves adding plant rosin materials together with spices or after spices to the product composition. Optionally, an emulsifier may be included to help the formation of particles in the final product. Preferred fragrance raw materials encapsulated in these self-assembled particles are those containing parts selected from cycloalkanes, cycloolefins, branched alkanes or their combinations. The particle size can be in the range of 10um to 90um.
[0092] When the perfume delivery system includes formaldehyde derivatives, such as perfume encapsulates with melamine-formaldehyde shells, the composition may also include a formaldehyde scavenger, which may include a sulfur-based formaldehyde scavenger, a non-sulfur-based formaldehyde scavenger, or a mixture thereof. Suitable non-sulfur-based formaldehyde scavengers may include urea, ethylene urea, acetoacetamide, or a mixture thereof. Suitable sulfur-based formaldehyde scavengers may include alkali metal and / or alkaline earth metal dithionites, pyrosulfites, sulfites, bisulfites, metasulfites, monoalkyl sulfites, dialkyl sulfites, dialkylene sulfites, sulfides, thiosulfates, thiocyanates, mercaptans, thioureas, and mixtures thereof.
[0093] Processing aids
[0094] The liquid conditioning compositions of the present disclosure may contain other processing adjunct ingredients. The adjunct ingredients may be selected to provide, for example, processing, stability and / or performance benefits.
[0095] Suitable processing aids may include surfactants, conditioning actives, deposition aids, rheology modifiers or structurants, bleach systems, stabilizers, builders, chelants, dye transfer inhibitors, dispersants, enzymes and enzyme stabilizers, catalytic metal complexes, polymeric dispersants, clay and soil removal / anti-redeposition agents, brighteners, suds suppressors, silicones, hueing agents, aesthetic dyes, additional perfumes and perfume delivery systems, structural elasticizers, carriers, hydrotropes, processing aids, structurants, anti-agglomeration agents, coatings, formaldehyde scavengers and / or pigments.
[0096] In particular, the liquid conditioning composition may further comprise a processing aid selected from the group consisting of additional conditioning agents, dyes, pH control agents, solvents, rheology modifiers, structurants, cationic polymers, surfactants, perfumes, perfume delivery systems, chelating agents, antioxidants, preservatives and mixtures thereof.
[0097] The specific nature of these additional components and their incorporation levels will depend on the physical form of the composition and the nature of the operation in which the resulting composition is used. However, when one or more adjuvants are present, such one or more adjuvants may be present as described in detail below. The following is a non-limiting list of adjuvant ingredients that may be useful.
[0098] 1. Rheology modifier / structurant
[0099] The liquid conditioning compositions of the present disclosure may include rheology modifiers and / or structurants. Rheology modifiers can be used to "thicken" or "thin down" a liquid composition to a desired viscosity. Structurants can be used to promote phase stability and / or suspend or inhibit aggregation of particles in a liquid composition, such as a perfume encapsulate as described herein.
[0100] Suitable rheology modifiers and / or structurants may include non-polymeric crystalline hydroxy-functional structurants (including those based on hydrogenated castor oil), polymeric structurants, cellulosic fibers (e.g., microfibrillated cellulose, which may be derived from bacteria, fungi, or plant sources, including from wood), diamido gelling agents, or combinations thereof.
[0101] The polymer structuring agent may be of natural or synthetic origin. Natural polymer structuring agents may include: hydroxyethyl cellulose, hydrophobically modified hydroxyethyl cellulose, carboxymethyl cellulose, polysaccharide derivatives and mixtures thereof. Polysaccharide derivatives may include: pectin, alginate, arabinogalactan (gum arabic), carrageenan, gellan gum, xanthan gum, guar gum and mixtures thereof. Synthetic polymer structuring agents may include: polycarboxylates, polyacrylates, hydrophobically modified ethoxylated polyurethanes, hydrophobically modified nonionic polyols and mixtures thereof. Polycarboxylate polymers may include polyacrylates, polymethacrylates or mixtures thereof. Polyacrylates may include C1-C12-C13-C16-C18-C19-C19-C18 ... 30 Copolymers of alkyl esters. Such copolymers are available from Noveon under the trade name Carbopol Aqua 30. Another suitable structurant is sold under the trade name Flosoft FS222 from SNF Floerger.
[0102] 2. Cationic polymers
[0103] Liquid conditioning compositions of the present disclosure may include cationic polymers. Cationic polymers may be used as deposition aids, for example, to promote improved deposition efficiency of softening and / or freshening actives on target surfaces. Additionally or alternatively, cationic polymers may provide stability, structuring and / or rheological benefits to the composition.
[0104] Liquid conditioning compositions may comprise from 0.0001% to 3%, preferably from 0.0005% to 2%, more preferably from 0.001% to 1%, or from about 0.01% to about 0.5%, or from about 0.05% to about 0.3%, by weight of the composition, of a cationic polymer.
[0105] In general, cationic polymers and methods for their manufacture are known in the literature. Suitable cationic polymers may include quaternary ammonium polymers known as "polyquaternium" polymers, as specified by the International Nomenclature for Cosmetic Ingredients, such as Polyquaternium-6 (poly(diallyldimethylammonium chloride)), Polyquaternium-7 (copolymer of acrylamide and diallyldimethylammonium chloride), Polyquaternium-10 (quaternized hydroxyethylcellulose), Polyquaternium-22 (copolymer of acrylic acid and diallyldimethylammonium chloride), and the like.
[0106] The cationic polymer may include a cationic polysaccharide, such as a cationic starch, a cationic cellulose, a cationic guar gum, or a mixture thereof. The cationic cellulose may include quaternized hydroxyethyl cellulose. Polymers derived from polysaccharides may be preferred, being naturally derived and / or sustainable materials.
[0107] Cationic polymers can include cationic acrylates. Cationic polymers can include cationic monomers, nonionic monomers and optional anionic monomers (as long as the total charge of the polymer is still cationic). Cationic polymers can include cationic monomers selected from the group consisting of the following items: dimethylaminoethyl acrylate ammonium quaternized by methyl chloride, dimethylaminoethyl methacrylate ammonium quaternized by methyl chloride and their mixtures. Cationic polymers can include nonionic monomers selected from the group consisting of acrylamide, dimethylacrylamide and their mixtures. Cationic polymers can optionally include anionic monomers selected from acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, and monomers that carry out sulfonic acid or phosphonic acid functions, such as 2-acrylamido-2-methylpropane sulfonic acid (ATBS), and their salts.
[0108] The cationic polymer may be substantially linear or may be cross-linked. The composition may include both substantially linear cationic polymers (e.g., formed from less than 50 ppm cross-linking agent) and cross-linked cationic polymers (e.g., formed from greater than 50 ppm cross-linking agent). Such combinations may provide both deposition and structuring benefits.
[0109] 3. Surfactants
[0110] Liquid conditioning compositions may contain less than 5%, or less than 2%, or less than 1%, or less than about 0.1% anionic surfactants by weight of the composition, or may even be substantially free of anionic surfactants. Anionic surfactants may adversely affect the stability and / or performance of the compositions of the present invention because they may undesirably interact with cationic components (such as conditioning compounds). Product compositions intended to be added during the rinse cycle of an automatic washing machine (such as liquid fabric enhancers) may contain relatively low levels of anionic surfactants. Additionally or alternatively, compositions intended to be used in combination with detergent compositions during the wash cycle of an automatic washing machine may contain relatively low levels of anionic surfactants.
[0111] The liquid conditioning composition may include a nonionic surfactant. Such surfactants may provide, for example, stability and / or processing benefits. The nonionic surfactant may be an emulsifier, such as a fragrance emulsifier. The nonionic surfactant may be an alkoxylated fatty alcohol, such as an ethoxylated C10-C18 fatty alcohol.
[0112] 4. Chelating agents
[0113] Liquid conditioning compositions may contain chelates (also referred to as chelating agents). Such agents may be iron and / or manganese and / or other metal ion chelating agents. Such chelating agents may be selected from the group consisting of aminocarboxylates, aminophosphonates, polyfunctionally substituted aromatic chelating agents, and mixtures thereof. If used, these chelating agents will typically comprise from about 0.1% to about 15%, preferably from about 0.1% to about 3.0%, by weight of the compositions described herein. More preferably, if used, chelating agents will comprise from about 0.1% to about 3.0% by weight of such compositions.
[0114] Suitable chelates may include: diethylenetriaminepentaacetic acid (DTPA); hydroxyethyldimethylenephosphonic acid (HEDP); MGDA (methylglycine diacetic acid); glutamic acid, N,N-diacetic acid (GLDA); 1,2-dihydroxybenzene-3,5-disulfonic acid (Tiron TM ); ethylenediamine disuccinate (EDDS); diethylenetriamine pentamethylenephosphonic acid (DTPMP); ethylenediaminetetra(methylenephosphonate); ethylenediaminetetraacetate; N-(hydroxyethyl)ethylenediaminetriacetate; nitrilotriacetate; ethylenediaminetetrapropionate; triethylenetetraaminehexaacetate; diethylenetriaminepentaacetate; ethanol diglycine; their alkali metal salts, ammonium salts or substituted ammonium salts; dihydroxydisulfobenzenes, such as 1,2-dihydroxy-3,5-disulfobenzene; and mixtures thereof.
[0115] 5. Antioxidants
[0116] The liquid conditioning composition may contain an antioxidant, preferably a phenolic antioxidant, more preferably a tocopherol antioxidant or a derivative thereof. The antioxidants in the compositions disclosed herein can be used for malodor control, cleaning performance and / or color stability because they can help reduce the yellowing that may be associated with amines. In addition, and without wishing to be bound by theory, it is believed that the presence of an antioxidant will reduce the auto-oxidation rate of the trans-unsaturated bonds of the esterquat fatty acid chain, and therefore can contribute to the viscosity stability of the composition. Antioxidants are substances as described in Kirk-Othmer (Volume 3, Page 424) and Ullmann's Encyclopedia (Volume 3, Page 91).
[0117] The compositions of the present disclosure may comprise an antioxidant, preferably a phenolic antioxidant, even more preferably tocopherol or a derivative thereof, in an amount of from about 0.001% to about 2%, preferably from about 0.01% to about 0.5% by weight of the composition.
[0118] A class of particularly preferred antioxidants for the disclosed compositions is tocopherol and derivatives thereof, such as tocotrienols. Such antioxidants are generally naturally derived, and therefore coupling with esterquat materials may be particularly interesting for sustainability / environmental reasons. In addition, due to the vitamin E activity of the compound, such compounds may be considered familiar, beneficial and safe by consumers. Tocopherols that can be used for the compositions of the present invention may include alpha-tocopherol, beta-tocopherol, gamma-tocopherol, delta-tocopherol or a combination thereof.
[0119] Other suitable antioxidants may include other phenolic antioxidants such as butylated hydroxytoluene ("BHT"; specifically, 3,5-di-tert-butyl-4-hydroxytoluene) and butylated hydroxyanisole ("BHA"). Other suitable antioxidants may include GXL TM , Trolox TM , Raluquin TM and / or by trade name Those that are sold.
[0120] 6. Preservatives
[0121] The liquid conditioning composition may include a preservative, which may contribute to the stability of the product when stored. The preservative may include a diphenyl ether antimicrobial agent, preferably 4-4'-dichloro-2-hydroxydiphenyl ether, 2,4,4'-trichloro-2'-hydroxydiphenyl ether, or a combination thereof. The preservative may include a quaternary ammonium antimicrobial agent, preferably a dialkyl quaternary ammonium antimicrobial agent. Suitable preservatives may include those sold under the trade names TINOSAN and / or BARQUAT.
[0122] 7. Additional Conditioning Agents
[0123] In addition to the above-mentioned esterquats, the liquid conditioning compositions of the present disclosure may also contain other conditioning agents. The additional conditioning agents may be selected from the group consisting of quaternary ammonium ester compounds other than those described above, silicones, non-ester quaternary ammonium compounds, amines, fatty esters, sucrose esters, silicones, dispersible polyolefins, polysaccharides, fatty acids, softening or conditioning oils, polymer latexes, glyceride copolymers, or combinations thereof.
[0124] The composition may include a combination of a quaternary ammonium ester compound and a silicone. The combined total amount of the quaternary ammonium ester compound and the silicone may be from about 5% to about 70%, or from about 6% to about 50%, or from about 7% to about 40%, or from about 10% to about 30%, or from about 15% to about 25%, by weight of the composition. The composition may include the quaternary ammonium ester compound and the silicone in a weight ratio of from about 1:10 to about 10:1, or from about 1:5 to about 5:1, or from about 1:3 to about 1:3, or from about 1:2 to about 2:1, or from about 1:1.5 to about 1.5:1, or about 1:1. When determining the amount of the quaternary ammonium ester compound as described in this paragraph, the amount may refer to the total amount of the esterquat as described in the previous section, or as described above, plus any additional quaternary ammonium ester compound that may be present.
[0125] Concentrated raw material composition
[0126] The present disclosure also relates to a concentrated raw material composition comprising the above-mentioned chitosan material, in particular a chitosan material having a weight average molecular weight (Mw) of 70 kDa to 600 kDa and a degree of deacetylation greater than 50%. For example, the chitosan material can be prepared and formulated into a concentrated raw material composition, which can then be stored and / or transported, and finally combined with adjuvant ingredients at another time or place to form a liquid conditioning composition according to the present disclosure.
[0127] The concentrated softening active composition may also include a liquid carrier. The liquid carrier may be selected from the group consisting of water, a surfactant or an organic solvent. Suitable surfactants may include nonionic surfactants, such as alkoxylated fatty alcohols. Suitable organic solvents may include propylene glycol, ethanol, isopropanol or propylene glycol.
[0128] Preparation method
[0129] The present disclosure relates to methods of making the liquid conditioning compositions described herein.A method of making a composition which may be a fabric enhancer composition may include the steps of mixing an amount of chitosan as described herein with an esterquat, a perfume, and one or more processing aids.
[0130] Liquid conditioning compositions of the present disclosure can be formulated into any suitable liquid form and prepared by any method selected by the formulator. Materials can be combined in batch methods, in a recycle loop method and / or by an online mixing method. Suitable equipment for the method disclosed herein may include a continuous stirred tank reactor, a homogenizer, a turbine agitator, a recirculation pump, a paddle mixer, a high shear mixer, a static mixer, a plow shear mixer, a ribbon blender, a vertical shaft granulator and a drum mixer (the two of which can be in an intermittent process configuration and a continuous process configuration (when available)), a spray dryer and an extruder.
[0131] The liquid conditioning composition may be placed in a pourable bottle by known methods.The liquid conditioning composition may be placed in an aerosol or other spray container according to known methods.
[0132] Treatment
[0133] The present disclosure also relates to methods of treating a surface (such as fabric or hair) with a liquid conditioning composition. Such methods can provide conditioning and / or refreshment benefits.
[0134] The method may include the step of contacting a surface, preferably a fabric, more preferably a fabric comprising cotton fibers, with a liquid conditioning composition of the present disclosure, optionally in the presence of water. The composition may be in a pure state or diluted in a liquid, such as a wash liquor or a rinse liquor. The composition may be diluted in water before, during or after contacting the surface or article. The surface, such as the fabric, may be optionally washed and / or rinsed before and / or after the contacting step. The composition may be applied directly to the fabric or provided to a dispensing container or drum of an automatic washing machine. The method may include drying the surface by, for example, passive drying and / or via an active method such as a laundry washing and drying machine. The method may occur during the wash cycle or rinse cycle, preferably the rinse cycle, of an automatic washing machine.
[0135] For purposes of this disclosure, treatment may include, but is not limited to, scouring and / or mechanical agitation. Fabrics may comprise most any fabric capable of being laundered or handled under normal consumer use conditions.
[0136] The liquid containing the disclosed composition may have a pH of about 3 to about 11.5. Such compositions are typically used at a concentration of about 500 ppm to about 15,000 ppm in solution when diluted. When the wash solvent is water, the water temperature is typically in the range of about 5°C to about 90°C, and the ratio of water to fabric may typically be about 1:1 to about 30:1.
[0137] use
[0138] The present disclosure also relates to the use of a chitosan material as described herein, preferably as part of a liquid conditioning composition, for improving the neat product odor of a liquid conditioning composition. It is believed that such use may be particularly attractive to consumers who desire good smelling products.
[0139] combination
[0140] Specific contemplated combinations of the present disclosure are described herein in the paragraphs with the following subscripts. These combinations are exemplary in nature and not limiting.
[0141] A. A liquid conditioning composition comprising from about 2% to about 8% by weight of the composition of an alkyl ester quaternary ammonium softening active, from 0.0001% to about 0.025% by weight of the composition of chitosan, and from 0.01 to about 5% by weight of the composition of free fragrance oil, wherein the composition has a viscosity of from about 80 cPs to about 300 cPs.
[0142] B. The liquid conditioning composition according to paragraph A, further comprising a perfume encapsulate.
[0143] C. The liquid conditioning composition of any of paragraphs A to B, wherein the fragrance encapsulate is present in the composition in an amount between about 0.05% and about 10%.
[0144] D. A liquid conditioning composition according to any of paragraphs A to C, wherein the fragrance encapsulate is characterized by a volume weighted median particle size of from about 1 micron to about 100 microns.
[0145] E. A liquid conditioning composition according to any of paragraphs A to D, wherein the perfume encapsulate is coated with a deposition aid, a cationic polymer, a nonionic polymer, an anionic polymer, or a mixture thereof.
[0146] F. A liquid conditioning composition according to any of paragraphs A to E, wherein the composition comprises from about 3% to about 7%, or more preferably from about 3% to about 6%, by weight of the composition, of an alkyl ester quaternary ammonium softening active.
[0147] G. A liquid conditioning composition according to any of paragraphs A to F, wherein the composition comprises from about 0.05% to about 4%, or more preferably from about 0.1% to about 3%, or more preferably from about 0.5% to about 2%, of free fragrance oil by weight of the composition.
[0148] H. A liquid conditioning composition according to any of paragraphs A to G, wherein the composition comprises from 0.001% to about 0.02%, or more preferably from about 0.0015% to about 0.015%, or more preferably from about 0.002% to about 0.01% chitosan by weight of the composition.
[0149] I. A liquid conditioning composition according to any of paragraphs A to H, wherein the composition has a viscosity of from about 90 cPs to about 250 cPs, or more preferably from about 150 cPs to about 250 cPs.
[0150] J. A liquid conditioning composition according to any of paragraphs A to I, wherein the liquid conditioning composition further comprises a processing aid selected from the group consisting of an additional conditioning agent, a dye, a pH control agent, a solvent, a rheology modifier, a structurant, a cationic polymer, a surfactant, a perfume, a perfume delivery system, a chelating agent, an antioxidant, a preservative or a mixture thereof; wherein the perfume delivery system, if present, preferably comprises a core-shell encapsulate.
[0151] K. A liquid conditioning composition according to any of paragraphs A to J, wherein the liquid conditioning composition comprises between about 0.05% and 2%, preferably less than 2%, preferably less than 1%, even more preferably less than 0.6% of a rheology modifier, structurant or mixture thereof.
[0152] L. A liquid conditioning composition according to any of paragraphs A to K, wherein the liquid conditioning composition comprises an antioxidant, preferably a phenolic antioxidant, more preferably tocopherol or a derivative thereof.
[0153] M. A method of treating a surface, the method comprising the steps of contacting a surface, preferably a fabric, more preferably a fabric comprising cotton fibers, with a liquid conditioning composition according to any one of paragraphs A to L, optionally in the presence of water.
[0154] N. Use of a liquid conditioning composition according to any of paragraphs A to M for softening fabrics.
[0155] O. A liquid conditioning composition according to any of paragraphs A to N, comprising from about 3% to about 6% of an alkyl ester quaternary ammonium softening active, by weight of the composition, from 0.002% to about 0.01% chitosan, by weight of the composition, and from 0.05 to about 2% free fragrance oil, by weight of the composition, wherein the composition has a viscosity of from about 150 cPs to about 250 cPs.
[0156] Test Method
[0157] Methods for assessing the degree of deacetylation
[0158] The following test method is used to determine the degree of deacetylation of chitosan. The degree of deacetylation of chitosan test material is determined by nuclear magnetic resonance (NMR) spectroscopy. Chitosan test material (10 mg) is dissolved in 1 mL of dilute acidic D2O (>99.9%, such as available from Aldrich). 1H NMR is measured at 298 Kelvin using a Brüker NMR instrument model DRX 300 spectrometer (300 MHz) (Bruker Corp., Billerica, Massachusetts, USA) or similar instrument. 1H NMR is represented by the signal of 3-(trimethylsilyl) propionic acid-2,2,3,3-d4 acid sodium salt (>98%, such as available from Aldrich) used as an external reference. Deacetylation is calculated by the measured chemical shift according to the standard and widely used method described in publication: Hirai et al., Polymer Bulletin 26 (1991), 87-94.
[0159] Method for determining dynamic yield stress
[0160] Dynamic yield stress is measured at 20°C using a controlled stress rheometer (such as HAAKE MARS or equivalent from Thermo Scientific) using 60 mm parallel plates and a gap size of 500 microns. The dynamic yield stress is obtained by measuring the quasi-steady-state shear stress as a function of shear rate, starting from 10 s-1 to 10-4 s-1, taking 25 points that are logarithmically distributed over the shear rate range. Quasi-steady state is defined as the shear stress value once the change in shear stress over time is less than 3% after at least 30 seconds and at most 60 seconds at a given shear rate. The change in shear stress over time is continuously evaluated by comparing the average shear stress measured over a 3 second period. If the shear stress value changes by more than 3% after measuring for 60 seconds at a certain shear rate, the final shear stress measurement is defined as the quasi-steady-state value for calculation purposes. The shear stress data are then fitted in logarithmic space using the least squares method as a function of shear rate, following the Herschel-Bulkley model:
[0161] T=To+ky"n
[0162] where T is the equilibrium quasi-steady-state shear stress measured at each applied shear rate y, and To is the fitted dynamic yield stress. k and n are fitting parameters.
[0163] Methods for evaluating the phase stability of LFE products
[0164] In order to evaluate the phase stability of the fabric enhancer product, the product is usually stored in one or several transparent 180 ml glass bottles, sealed with lids. These glass bottles are then placed in a constant temperature room (e.g., 25°C or 35°C). The phase stability of the fabric enhancer product is then evaluated by a person skilled in the art after a certain period of time, such as once a week for 1 month, followed by monthly inspections. In order to be able to see the visual indication of minimal phase instability, the observer needs to observe the entire sample very carefully. The bottom of the glass bottle also needs to be carefully observed. Preferably, a bright light or lamp is used to illuminate the sample.
[0165] When evaluating the phase stability of a number of samples, a phase separation grading scale can be used that allows the visual grading to be converted into numbers. Table 1 below shows the phase stability grading scale for the fabric enhancers described and tested herein. A picture of each failure grade is also provided.
[0166] Table 1
[0167]
[0168]
[0169] Figure 1 An example of a Failure Level 1 is shown, which is a very small crack that appeared at the bottom of a clear glass bottle. The added arrow points to the crack that appeared in the sample, i.e., a visual indication of very slight phase separation. These very small cracks can sometimes be difficult to discern and are usually only visible when the sample is illuminated with bright light. Failure Level 1 cracks are usually only visible at the bottom of the clear glass bottle.
[0170] Figure 2 An example of a Failure Level 2 is shown, which is a crack on the bottom of a clear glass bottle. Failure Level 2 is easier to discern than Failure Level 1, but using a bright light to illuminate the sample still helps. Failure Level 2 typically has multiple visible cracks, and the cracks are more obvious than cracks that only meet Failure Level 1. Failure Level 2 cracks are typically only visible on the bottom of the clear glass bottle.
[0171] Figure 3 An example of Failure Level 3 is shown, which is one or more large cracks on the bottom of a clear glass bottle. Failure Level 3 cracks are usually only visible on the bottom of the clear glass bottle, but can sometimes be seen on the sides of the bottle.
[0172] Figure 4 An example of Failure Level 4 is shown, which is the occurrence of phase separation of less than 5% of the sample material in the clear glass bottle. Failure Level 4 cracks are typically visible on the bottom of the clear glass bottle as well as on the sides of the bottle. Figure 4 The phase separation is shown as viewed from the side of the bottle, located at the bottom portion of the bottle.
[0173] Figure 5 An example of Failure Level 5 is shown, which is the occurrence of phase separation of greater than 5% of the sample material in the clear glass bottle. Failure Level 5 cracks are typically visible on the bottom of the clear glass bottle (two samples are shown) as well as on the sides of the bottle. Figure 5 The phase separation is shown as viewed from the side of the bottle, located at the bottom portion of the bottle.
[0174] Method for determining the headspace concentration above liquid fabric enhancers
[0175] Liquid fabric enhancers were analyzed by a fast headspace GC / MS (gas chromatography mass spectrometry) method. 1 g aliquots of liquid fabric enhancers were transferred to 25 ml headspace vials and capped. The headspace vials were equilibrated at 30°C for 10 minutes. The headspace above the liquid solution was sampled for 5 minutes via the SPME (50 / 30 μm DVB / Carboxen / PDMS) method. The SPME fiber was then thermally desorbed immediately into the GC. The analytes were analyzed by fast GC / MS in full scan mode. The total HS response and the fragrance headspace composition above the tested liquid fabric enhancers were calculated using ion extraction of specific mass of the PRM.
[0176] Method for determining headspace concentrations above treated wet and dry fabrics
[0177] Cotton tracers were analyzed by a fast headspace GC / MS (gas chromatography mass spectrometry) method. A 4×4 cm aliquot of terry towel cotton tracer was transferred to a 25 mL headspace vial. The fabric sample was equilibrated at 65°C for 10 minutes. The headspace above the fabric was sampled for 5 minutes via the SPME (50 / 30 μm DVB / Carboxen / PDMS) method. The SPME fiber was then thermally desorbed immediately into the GC. The analytes were analyzed by fast GC / MS in full scan mode. The total HS response and fragrance headspace composition above the test leg were calculated using mass-specific ion extraction of the PRM.
[0178] Method for determining the encapsulated oil content in liquid fabric enhancers
[0179] An aliquot was diluted into water. The fragrance microcapsules were isolated by filtration (5 micron filter). After incorporation of an internal standard and addition of ethanol, the fragrance was released by heating to 60°C for half an hour. The encapsulated fragrance content was analyzed by GC / MS via internal standard calibration.
[0180] Determination of polymer molecular weight and related parameters
[0181] Molecular weight distribution measurements and related values for the polymers described herein were found using the following method describing gel permeation chromatography with multi-angle light scattering and refractive index detection (GPC-MALS / RI).
[0182] Gel Permeation Chromatography (GPC) with Multi-Angle Light Scattering (MALS) and Refractive Index (RI) detection (GPC-MALS / RI) allows the absolute molecular weight of polymers to be measured without the need for column calibration methods or standards. The GPC system allows molecules to be separated according to their molecular size. MALS and RI allow information on the number average (Mn) and weight average (Mw) molecular weight to be obtained.
[0183] The Mw distribution of water-soluble polymers such as chitosan is usually measured by using a liquid chromatography system (e.g., Agilent 1260 Infinity pump system with OpenLabChemstation software, Agilent Technology, Santa Clara, CA, USA) and a column set (e.g., 2 Tosoh TSKgel G6000WP 7.8×300mm 13um pore size, guard column A0022 6mm×40mm PW xl-cp, King of Prussia, PA) operated at 40°C. The mobile phase is a 0.1 M sodium nitrate aqueous solution containing 0.02% sodium azide and 0.2% acetic acid. The mobile phase solvent is pumped isocratically at a flow rate of 1 mL / min. The column was prepared using a Wyatt Multi-angle light scattering (18-Angle MALS) detector controlled by software v8.0 and a differential refractive index (RI) detector (Wyatt Technology, Santa Barbara, California, USA).
[0184] Samples were typically prepared by dissolving the chitosan material at about 1 mg / ml in the mobile phase and hydrated by mixing the solution overnight at room temperature. Prior to GPC analysis, samples were filtered through a 0.8 μm Versapor membrane filter (PALL, Life Sciences, NY, USA) using a 3 ml syringe into an LC autosampler vial.
[0185] The number average molecular weight (Mn), weight average molecular weight (Mw), Z average molecular weight (Mz), molecular weight of the peak maximum (Mp) and polydispersity (Mw / Mn) were determined by the Astra detector software using the dn / dc value (differential change of refractive index with concentration, 0.15).
[0186] Example
[0187] The examples provided below are intended to be illustrative in nature and not intended to be limiting.
[0188] Table 2 shows exemplary liquid conditioning compositions according to the present disclosure. Specifically, the following compositions are intended as liquid fabric enhancer products.
[0189] Table 2
[0190]
[0191] *Core-shell fragrance capsules. The "% Active" provided is the amount of fragrance delivered to the composition.
[0192] Example 1. Pure product odor .
[0193] Four liquid treatment compositions (fabric enhancer products) were prepared by a person skilled in the art according to the formulations provided in Table 3 below.
[0194] Table 3
[0195]
[0196] The headspace strength above the neat products was then evaluated according to the method for determining the headspace concentration above the liquid fabric enhancer as detailed herein. Surprisingly, the headspace strength above the compositions containing 0.01% chitosan (Composition 2 and Composition 4) was found to be significantly higher than the headspace strength above the reference products without chitosan (Composition 1 and Composition 3). The results are shown in Figure 6 , which shows the pure product odor headspace for each of the four examples detailed above. In fact, Composition 2 and Composition 4 have significantly higher headspace (450 nmol / L and 435 nmol / L) than Compositions 1 and 3 (397 nmol / L and 410 nmol / L), respectively.
[0197] Example 2. Fabric Enhancer Phase Stability as a Function of Chitosan Level
[0198] First, a fabric enhancer product was prepared according to the composition in Table 4 below:
[0199] Table 4
[0200]
[0201]
[0202] In the second step, the product was divided into 11 180 ml glass bottles. Different levels of chitosan were added to each of these bottles containing the product while mixing for 2 minutes with an IKA overhead mixer without introducing air. The chitosan used was acid treated (as described herein) with a molecular weight of 200 kDa to 250 kDa and a DDA (degree of deacetylation) between 80% and 85%. The different levels of chitosan and the measured composition viscosities are detailed in Table 5 below.
[0203] Table 5
[0204]
[0205] These products were then stored at 35°C for 4 hours.
[0206] In the third step, the phase stability of each composition was evaluated after 4 weeks of storage at 35° C. according to the method for evaluating the phase stability of LFE products detailed herein. The phase stability failure rating evaluation scores are shown in Table 6 below.
[0207] Table 6
[0208]
[0209]
[0210] From Table 6 above, it can be seen that up to about 0.02% chitosan level in the fabric enhancer composition, the phase stability evaluation is no worse than a failure level of 1. Generally, when a consumer purchases a bottle of a fabric enhancer product at a store, they expect it to be phase stable. It is expected that a failure level evaluation above 2 will disappoint the consumer because the untrained eye will see phase separation. A failure level evaluation of 1 or 0 is generally accepted by the consumer.
[0211] Example 3. Triethanolamine-based esterquat / phase stability of commercial liquid fabric enhancer with chitosan water Flat functional relationship .
[0212] In each of two glass bottles, 180 ml of a commercial liquid fabric softener Robijn "Puur enZacht" (Unilever) was poured. The fabric softener comprises a triethanolamine-based esterquat. Different levels of chitosan were added to each of these bottles containing the liquid fabric softener product and mixed for 2 minutes with an IKA overhead mixer without introducing air. The different levels of chitosan and the measured composition viscosities are detailed in Table 7 below.
[0213] Table 7
[0214]
[0215] These products were then stored at 35°C for 4 hours.
[0216] After storage at 35°C for 4 weeks, the phase stability of each composition was evaluated according to the method for evaluating the phase stability of LFE products detailed herein. The phase stability failure rating evaluation scores are shown in Table 8 below.
[0217] Table 8
[0218]
[0219] A picture of the failure level 4 phase separation observed in composition A after 4 weeks at 35°C can be seen at Figure 7 There is an arrow pointing to the bottle logo to visually separate the parts.
[0220] It can be noted from Tables 7 and 8 above that the high levels of chitosan added to Robijn "Puur en Zacht" resulted in a Failure Level 4 phase separation, whereas the Puur en Zacht product with low levels of chitosan showed no phase instability at all.
[0221] The dimensions and values disclosed herein are not to be understood as being strictly limited to the exact numerical values cited. Instead, unless otherwise indicated, each such dimension is intended to represent the stated value and a functionally equivalent range around that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm".
[0222] Unless expressly excluded or otherwise limited, each document cited herein, including any cross-referenced or related patent or patent application and any patent application or patent to which this application claims priority or the benefit of, is hereby incorporated by reference in its entirety. The citation of any document is not an admission that it is prior art to any of the present invention disclosed or claimed herein, or an admission that it, by itself or in combination with any one or more of the references, proposes, suggests, or discloses any such invention. In addition, to the extent that any meaning or definition of a term in this invention conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this invention shall govern.
[0223] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.
Claims
1. A liquid conditioning composition, comprising: 2% to 8% by weight of the composition of an alkyl ester quaternary ammonium softening active, 0.0001% to 0.025% chitosan by weight of the composition, and 0.01% to 5% by weight of the composition of free fragrance oil, The composition has a viscosity of 80 cPs to 300 cPs.
2. The liquid conditioning composition of claim 1 further comprising a perfume encapsulate.
3. A liquid conditioning composition according to any preceding claim wherein the perfume encapsulate is present in the composition in an amount of between 0.05% and 5% by weight of the composition.
4. A liquid conditioning composition according to claim 2 or 3 wherein the fragrance encapsulate is characterised by a volume weighted median particle size of from 1 micron to 100 microns.
5. A liquid conditioning composition according to claims 2 to 4, wherein the perfume encapsulate is coated with a deposition aid, a cationic polymer, a nonionic polymer, an anionic polymer or mixtures thereof.
6. A liquid conditioning composition according to any preceding claim wherein the composition comprises from 3% to 7%, or more preferably from 3% to 6%, by weight of the composition, of an alkyl ester quaternary ammonium softening active.
7. A liquid conditioning composition according to any preceding claim wherein the composition comprises from 0.05% to 4%, or more preferably from 0.1% to 3%, or more preferably from 0.5% to 2%, by weight of the composition, of free perfume oil.
8. A liquid conditioning composition according to any preceding claim wherein the composition comprises from 0.001% to 0.02%, or more preferably from 0.0015% to 0.015%, or more preferably from 0.002% to 0.01% chitosan by weight of the composition.
9. A liquid conditioning composition according to any preceding claim, wherein the composition has a viscosity of from 90 cPs to 250 cPs, or more preferably from 150 cPs to 250 cPs.
10. A liquid conditioning composition according to any preceding claim, wherein the liquid conditioning composition further comprises a processing aid selected from the group consisting of: additional conditioning agents, dyes, pH control agents, solvents, rheology modifiers, structurants, cationic polymers, surfactants, perfumes, perfume delivery systems, chelating agents, antioxidants, preservatives or mixtures thereof; wherein the perfume delivery system, if present, preferably comprises a core-shell encapsulate.
11. A liquid conditioning composition according to any preceding claim, wherein the liquid conditioning composition comprises between 0.05% and 2%, preferably less than 2%, preferably less than 1%, even more preferably less than 0.6% of a rheology modifier, structurant or mixtures thereof.
12. A liquid conditioning composition according to any preceding claim, wherein the liquid conditioning composition comprises an antioxidant, preferably a phenolic antioxidant, more preferably tocopherol or a derivative thereof.
13. A method for treating a surface, the method comprising the steps of: A surface, preferably a fabric, more preferably a fabric comprising cotton fibres, is contacted with a liquid conditioning composition according to any preceding claim, optionally in the presence of water.
14. Use of a liquid conditioning composition according to any preceding claim for softening fabrics.
